Value Added Tax on Financial Services in the EU: The Complete Story - Antonov, Lyubomir (Review of European and Comparative Law, 2024)
The paper provides an extensive overview of the VAT exemption of financial services in the EU. The topic is surrounded by conceptual and practical challenges. The main issues are presented in a retrospective plan. They have been clearly defined and discussed since the very inception of the EU VAT system. The difficulties this tax regime is faced with today reveal the logical sequence that can be traced as far back as the 1970s. In its first part, the paper looks at the topic from a historical perspective, exploring the inclusion of financial services within the scope of the first VAT rules. Further insight is subsequently provided on the application of the VAT exemption over the past decades until the present-day rules. At its core, the text relies mostly upon the CJEU case law. Capital issues for VAT fiscal neutrality are also given careful consideration. This is the major concern inspiring the Commission’s attempts and proposals for VAT reforms. After a concise examination of the efforts to revise the legislation, the paper focuses on the most recent developments in the financial industry, which is a major stakeholder concerned by the recent aspirations of Brussels.